Responsibility-Sharing in the Giving and Receiving of Assessment Feedback - Nash, Robert A.; Winstone, Naomi E. (Frontiers in Psychology, 2017)
Many argue that effective learning requires students to take a substantial share of responsibility for their academic development, complementing the responsibilities taken by their educators. Yet this notion of responsibility-sharing receives minimal discussion in the context of assessment feedback, where responsibility for enhancing learning is often framed as lying principally with educators. Developing discussion on this issue is critical: many barriers can prevent students from engaging meaningfully with feedback, but neither educators nor students are fully empowered to remove these barriers without collaboration. In this discussion paper we argue that a culture of responsibility-sharing in the giving and receiving of feedback is essential, both for ensuring that feedback genuinely benefits students by virtue of their skilled and proactive engagement, and also for ensuring the sustainability of educators’ effective feedback practices. We propose some assumptions that should underpin such a culture, and we consider the practicalities of engendering this cultural shift within modern higher education.